Protective effect of intranasal immunization with Neospora caninum membrane antigens against murine neosporosis established through the gastrointestinal tract. Issue 2 (February 2014) - Ferreirinha, Pedro; Dias, Joana; Correia, Alexandra; Pérez‐Cabezas, Begoña; Santos, Carlos; Teixeira, Luzia; Ribeiro, Adília; Rocha, António; Vilanova, Manuel
Summary Neospora caninum is an Apicomplexa parasite that in the last two decades was acknowledged as the main pathogenic agent responsible for economic losses in the cattle industry. In the present study, the effectiveness of intranasal immunization with N. caninum membrane antigens plus CpG adjuvant was assessed in a murine model of intragastrically established neosporosis. Immunized mice presented a lower parasitic burden in the brain on infection with 5 × 107 tachyzoites, showing that significant protection was achieved by this immunization strategy. Intestinal IgA antibodies raised by immunization markedly agglutinated live N. caninum tachyzoites whereas previous opsonization with IgG antibodies purified from immunized mice sera reduced parasite survival within macrophage cells. Although an IgG1 : IgG2a ratio < 1 was detected in the immunized mice before and after infection, indicative of a predominant T helper type 1 immune response, no increased production of interferon‐γ was detected in the spleen or mesenteric lymph nodes of the immunized mice. Altogether, these results show that mucosal immunization with N. caninum membrane proteins plus CpG adjuvant protect against intragastrically established neosporosis and indicate that parasite‐specific mucosal and circulating antibodies have a protective role against this parasitic infection.